Results in Education of the First Albanian Government - Mehmeti , Nevila (European Journal of Multidisciplinary Studies, 2022)
The aim of the paper named Results in Education of the First Albanian Government is to reflect the efforts and results of Vlora’s government in the area of education, as seen from the perspective of archive historic documents, press of that time and different monographies of Albanian and foreign authors. This paper clearly details the phases whereby learning Albanian process passes into, that starts with opening of schools and their expansion in many areas of the country, but also with legal, administrative and educational measures in assisting a normal educational process, in the context of that historic period. In the research work conducted for this paper, preliminary research is used. It needs to be highlighted that the collected facts and evidences are based qualitative and quantitative methods. The question if Vlora’s government was able to achieve progress in education in about a 14 months period is answered in the Results section, where there are treated some of the most important matters of the Albanian national education. In a final analysis, the achievements of Vlora’s government in the national education area, must be considered having in mind the political situation, financial means and educational heritage in Albania.